Managing a newspaper post press system installation - a proposal to C.C.P.M approach - Tsui, Wing Tai. (2008)
Explore a case study on project management involved in an installation project for a local Newspaper printing plant and to explore the possibility of implementing Critical Chain Project Management into the project for future benefits.